PENERAPAN STANDAR HYGIENE DAN SANITASI DALAM OPERASIONAL DAPUR HOTEL: STUDI KASUS F&B PRODUCT HOTEL ARYADUTA MANADO - Agustinus Walansendow; Bet El SIlisna Lagarense; Helni Desty Yanice Lagarense (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
The implementation of hygiene and sanitation standards is a crucial aspect of hotel kitchen operations, particularly in the Food and Beverage (F&B) Product Department. These practices include maintaining the cleanliness of kitchen equipment, ensuring hygienic behavior among kitchen staff, and handling food ingredients safely and properly. This study aims to analyze the application of hygiene and sanitation standards in food production processes and to identify key factors that must be considered to produce high-quality and safe food products. This research employs a descriptive qualitative approach, with data collected through direct observation, interviews, and documentation. The findings reveal that some staff members in the F&B Product Department of Aryaduta Hotel Manado have not fully implemented proper hygiene and sanitation standards during food processing. Several hygiene procedures are still neglected in daily kitchen operations, although some staff have shown good adherence to these standards. These findings highlight the need to improve compliance with hygiene and sanitation procedures to ensure the quality and safety of food served to hotel guests. Keywords: hygiene and sanitation, product quality, hotel kitchen, F&B kitchen